PREVALENSI PASIEN HEMODIALISA YANG TERINFEKSI COVID-19 DI JAKARTA UTARA - Mastika Chusnul Khotimah (2021)
Covid-19 is a new pandemic that can cause respiratory problems and pneumonia. CKD patients undergoing hemodialysis are included in the risk group for Covid-19 infection. However, the prevalence of hemodialysis patients infected with Covid-19 has not been widely reported. This research aims to determine the prevalence of hemodialysis patients infected with Covid-19 in North Jakarta represented by two hospitals in North Jakarta, namely RSUD Koja and RSIJ Sukapura. This study used a descriptive design with retrospective approach. A total of 90 hemodialysis patients infected with Covid-19 in North Jakarta were reported in this research. A total of 48 patients were male (53.3%) and 42 female patients (46.7%) with an average age of 50.5 years and a median age of 52 years. A total of 35 patients had comorbid diabetes mellitus, 65 patients had heart disease/hypertension, 5 patients had hepatitis, and 3 patients had other diseases than those mentioned. Most patients treated in December 2020. The majority of patients experienced some symptoms such as shortness of breath/dyspnea (15,5%), weakness (12,6%), cough (11,7%), nausea (11,2%), and fever (8,0%). The high number of patients reinforces the need to take appropriate infection control measures to prevent the spread of COVID-19 in this vulnerable population.